UU TENTANG PENGELOLAAN ZAKAT VERSUS FATWA KYAI LOKAL (Studi di Desa Tanggungharjo Kecamatan dan Kabupaten Grobogan Jawa Tengah) - Yasin, Yasin (ZISWAF, 2015)
Paying zakat, a muslim repairing his relationship to the creator and his relationship with fellow human beings. Therein lies the primacy of worship this zakat. The idea of implementing the obligations of charity towards all the results of the efforts of the economic value of the service sector as well as the profession has not been fully accepted by Muslims in Indonesia.